TRANSIENT CIRCUIT SIMULATION OF ARC-FREE CURRENT BREAKING BY RESISTANCE RISE Č - Bin Khalid, Dareer; Rock, Michael; Piegari, Luigi (Journal of Energy Technology, 2023)
There has been intensive research and development in the field of Circuit breakers, whether DC and AC, or low voltage and high voltage. The result of this has led to the production of highly reliable circuit breakers that accompany a built-in arc extinguishing system. However, the purpose of this study is to give the basics for arc-free current breaking with fast interruption of fault currents, e.g., in surge protective devices (SPD) for AC and DC systems, by means of a time-dependent resistor with fast rising resistance. This investigation shall illustrate how the current can be driven almost to zero with a steadily time increasing resistance, and interrupted completely without an electric arc. The basic aim of the conducted transient circuit simulations is to determine suitable time functions for the current or resistance and necessary initial and final resistances. This paper will discuss the "optimisation conditions", a switching time as short as possible, small switch-off overvoltage, and possibly an energy conversion in the resistor as low as possible is set using ATP-EMTP and analytical calculations.
Keywords: current breaking; ATP-EMTP; time-dependent resistance; optimisation; concave & convex functions